Super-compact bandpass filter based on a novel resonator composed of two strongly-coupled λ/4 sub-resonators - Zhang, Songbai (2013)
This paper proposes and develops a novel resonator, which is composed of two strongly-coupled λ/4 sub-resonators via an interdigital capacitor. Firstly, two strongly-coupled Stepped Impedance Resonators (SIRs) are considered as a single resonator and its resonant properties are investigated theoretically. Secondly, to realize the strong mutual coupling, the low impedance end of SIR is split to form an interdigital capacitor. The resultant resonator shows a competitive merit in size miniaturization. Meanwhile, this structure is similar with the Zeroth Order Resonator (ZOR) in composite right/left handed (CRLH) transmission line (TL) metamaterial, while our perspective demonstrates a distinctive advantage on the understanding of resonant modes. Furthermore, a super-compact bandpass filter based on two parallel-connected resonators is designed, which not only shows the sharp rejection skirts at both low and high cut-off frequencies of the desired passband, but also possesses good spurious suppression.